2012
DOI: 10.1016/j.jstrokecerebrovasdis.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cost of Pneumonia After Stroke for Different Risk Groups

Abstract: Introduction-An evidenced based approach to detecting and treating dysphagia needs to be informed by costs and risks associated with pneumonia. In this study the cost of pneumonia during hospitalization after stroke and the effect of pneumonia on mortality were estimated. The effect of pneumonia on mortality and cost for different levels of risk were also analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 24 publications
3
110
0
8
Order By: Relevance
“…Another classification in use divides SAP into acute (when pneumonia develops within a month of stroke) and chronic (when it occurs later than a month) [10]. Clinical SAP studies used a wide range of criteria to define SAP starting from the Center of Disease Control and Prevention criteria to investigating ventilator-associated pneumonia after stroke to reviewing patients' diagnosis from the charts [1,5,12]. We will use the Center of Disease Control and Prevention criteria to define nosocomial pneumonia [13], as they are the most widely used ones among the studies [14,15].…”
Section: Definitions and General Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another classification in use divides SAP into acute (when pneumonia develops within a month of stroke) and chronic (when it occurs later than a month) [10]. Clinical SAP studies used a wide range of criteria to define SAP starting from the Center of Disease Control and Prevention criteria to investigating ventilator-associated pneumonia after stroke to reviewing patients' diagnosis from the charts [1,5,12]. We will use the Center of Disease Control and Prevention criteria to define nosocomial pneumonia [13], as they are the most widely used ones among the studies [14,15].…”
Section: Definitions and General Termsmentioning
confidence: 99%
“…Post-stroke pneumonia also increases the financial burden on the medical system. The annual cost of this complication approaches USD 459 million [4] and the average marginal cost of hospitalization is USD 27,633 [5]. These factors reflect the importance of preventing this complication.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that stroke-induced immune suppression increases the risk of secondary infections and increases mortality rates in patients [16,17]. Up to 65 % of patients with stroke suffer from pneumonia and urinary tract infections [18,19], and approximately 30 % of them die from stroke-related infections [20][21][22]. Studies focusing on the innate immune system have shown that stroke impairs the respiratory burst and subsequent generation of inflammatory mediators in granulocytes and monocytes [23,24].…”
Section: Impact Of Stroke On Immunitymentioning
confidence: 99%
“…1,2 Cerebrovascular diseases or stroke is the third most frequent cause of death in developed countries, only after heart disease and cancer. 3 It has been observed that subjects who have had a cerebrovascular accident have weak respiratory muscles.…”
Section: Introductionmentioning
confidence: 99%